The Feasibility and Efficacy of a Serial Reaction Time Task that Measures Motor Learning of Anticipatory Stepping - Olivier, Geneviève N. (Gait Posture, 2021)
BACKGROUND: Motor learning has been investigated using various paradigms, including serial reaction time tasks (SRTT) that examine upper extremity reaching and pointing while seated. Few studies have used a stepping SRTT, which could offer additional insights into motor learning involving postural demands. For a task to measure motor learning, naïve participants must demonstrate a) improved performance with task practice, and b) a dose-response relationship to learning the task. RESEARCH QUESTION: Is a stepping SRTT feasible and efficacious for measuring motor learning? Methods: In this prospective study, 20 participants stood on an instrumented mat and were presented with stimuli on a computer screen. They stepped to the corresponding positions on the mat as quickly as possible. Presented stimuli included random sequences and a blinded imbedded repeating sequence. Three days after completing the randomly assigned practice dose [high dose group (n=10) performed 4320 steps; low dose group (n=10) performed 144 steps], a retention test of 72 steps was performed. Feasibility was measured as the proportion of participants who completed the assigned practice dose without adverse events. Efficacy was measured as within-group performance improvement on the random sequences and on the repeating sequence (paired t-tests), as well as a dose-response relationship to learning both types of sequences (independent t-tests). RESULTS: All participants (mean age 26.8 years) completed all practice sessions without adverse events, indicating feasibility. High dose practice resulted in performance improvement while low dose did not; a dose-response relationship was found, with high dose practice resulting in greater learning of the task than low dose practice, indicating efficacy. SIGNIFICANCE: This stepping SRTT is a feasible and efficacious way to measure motor learning, which could provide critical insights into anticipatory stepping, postural control, and fall risk. Future research is needed to determine feasibility, efficacy, and optimal practice dosages for older and impaired populations.